Rotor airfoil aerodynamic design method and test verification - He, L.; Sun, J.; Zhang, W.; Wu, J. (My University, 2018)
Good airfoil design is a prerequisite for high performance rotor design. In order to establish the rotor airfoil design method and verify the wind tunnel data, this paper developed an efficient multi-objective and multi-constraint optimization design system for rotor airfoils, which is based on high-precision CFD analysis. And using OA309 as the baseline rotor airfoil, the CRA09 optimized rotor airfoil was designed successfully. Combined with the foundation of high-precision rotor airfoil stationary test technology, the CRA09 and OA309 rotor airfoils were tested in the S3MA high speed wind-tunnel of ONERA and the FL-21 high speed wind-tunnel of CARDC. Results indicate that, multi-objective and multi-constraint optimization design method developed in this study is reliable; CRA09 optimized airfoil provides better stationary performance than OA309 airfoil, in terms of maximum lift coefficient and lift over drag ratio.